Scientific and Technical Capacity of Regions as the Foundation for Technological Independence of the Russian Federation - Golova , Irina M. Golova (Economy of Regions, 2022)
Technological independence is one of the key challenges for modern Russia. Solution of this problem requires the consideration of the scientific and technical capacity of Russian regions. This study aims to define the scientific and technical capacity of regions; to create a methodology for managing capacity building; to develop methodological approaches to increase the ability of the scientific and technical capacity of regions to ensure the technological independence. The research used statistical data from the Organisation for Economic Co-operation and Development (OECD), Federal Customs Service of Russia, Federal State Statistics Service (Rosstat), and other sources. Analysis of the import dependence of Russia shows that the rate of coverage of imports by exports for the majority of high-tech goods does not exceed 5–10 %. The study identified barriers to the development of the scientific and technical capacity of Russian regions: technological backwardness and financial instability of the high-tech sector, low willingness to update, imbalance in the structure of the scientific and technical capacity, etc. A methodology for overcoming these barriers based on an integrated approach to regional innovation processes was presented. Additionally, a methodological approach to enhancing the interaction between science and business relying on the open innovation model was proposed. Calculations performed using the hierarchical cluster analysis revealed a group of the most promising regions for the establishment of innovative development centres. Three clusters were identified (in descending order of priority): leading (4 constituent entities), advanced (6 constituent entities) and developed (3 constituent entities) regions. The obtained results can be used to manage regional scientific and technological development and create the methodology for innovative transformation of the Russian economy.